Factors impacting knowledge and use of long acting and permanent contraceptive methods by postpartum HIV positive and negative women in Cape Town, South Africa: a cross-sectional study - Credé Sarah; Hoke Theresa; Constant Deborah; Green Mackenzie S; Moodley Jennifer; Harries Jane (BMC, 2012)
Abstract Background The prevention of unintended pregnancies among HIV positive women is a neglected strategy in the fight against HIV/AIDS. Women who want to avoid unintended pregnancies can do this by using a modern contraceptive method. Contraceptive choice, in particular the use of long acting and permanent methods (LAPMs), is poorly understood among HIV-positive women. This study aimed to compare factors that influence women's choice in contraception and women's knowledge and attitudes towards the IUD and female sterilization by HIV-status in a high HIV prevalence setting, Cape Town, South Africa. Methods A quantitative cross-sectional survey was conducted using an interviewer-administered questionnaire amongst 265 HIV positive and 273 HIV-negative postpartum women in Cape Town. Contraceptive use, reproductive history and the future fertility intentions of postpartum women were compared using chi-squared tests, Wilcoxon rank-sum and Fisher's exact tests where appropriate. Women's knowledge and attitudes towards long acting and permanent methods as well as factors that influence women's choice in contraception were examined. Results The majority of women reported that their most recent pregnancy was unplanned (61.6% HIV positive and 63.2% HIV negative). Current use of contraception was high with no difference by HIV status (89.8% HIV positive and 89% HIV negative). Most women were using short acting methods, primarily the 3-monthly injectable (Depo Provera). Method convenience and health care provider recommendations were found to most commonly influence method choice. A small percentage of women (6.44%) were using long acting and permanent methods, all of whom were using sterilization; however, it was found that poor knowledge regarding LAPMs is likely to be contributing to the poor uptake of these methods. Conclusions Improving contraceptive counselling to include LAPM and strengthening services for these methods are warranted in this setting for all women regardless of HIV status. These study results confirm that strategies focusing on increasing users' knowledge about LAPM are needed to encourage uptake of these methods and to meet women's needs for an expanded range of contraceptives which will aid in preventing unintended pregnancies. Given that HIV positive women were found to be more favourable to future use of the IUD it is possible that there may be more uptake of the IUD amongst these women.